Comparison of Landslide Disaster Risk Assessment Standards: A Study of Indonesia’s Ministry of Public Works Regulations and Malaysia’s Slope Assessment System - Muhammad Mukhlisin,; Iwanudin,; Rini Kusumawardani,; Hany Windri Astuti,; Roni Apriantoro,; Amin Suharjono, (International Journal of Integrated Engineering, 2025)
Semarang City is an area prone to landslides, especially areas with hilly morphology. The landslide incident certainly brought losses in both lives and material. Seeing that there are landslides in several areas of Semarang City, an assessment is needed so that landslide disasters can be anticipated. This research is located on the slope of Building E10, Faculty of Engineering, Semarang State University. This research aims to determine the level of risk of vulnerability to landslides using the Regulation of the Minister of Public Works of the Republic of Indonesia Number 22 of 2007 and the Slope Assessment Systems Method. The results of the two methods were compared with the finite element method using the Plaxis 8.6 program. The vulnerability level value based on Minister of Public Works Republic of Indonesia Regulation Number 22 of 2007 on slope 1 is 2.44, which is included in the category of a high level of landslide vulnerability, while the value for slope 2 is 2.156, which is included in the moderate level of landslide vulnerability. The assessment results using the Slope Assessment System (Slope Management and Risk Tracking System) method for Slope 1 were 0.957, which was included in the very high level of vulnerability category, while for Slope 2, it was 0.8926, which was included in the very high level of landslide vulnerability category. The results of the finite element method with the Plaxis 8.6 program show that the value of the safety factor on the slope of Building E10, Faculty of Engineering, Semarang State University, is 0.604 and is included in unstable soil conditions.